PERFORMANCE OF SUPER EARLY PIGEONPEA IN DIFFERENT SOWING WINDOWS AND INTEGRATED NUTRIENT MANAGEMENT IN SOUTHERN TELANGANA ZONE - JAYASREE. G; SREEKANTH. P. D, PARIMALA KUMAR. M, SUNEETHA DEVI. K. B, BALAJI NAIK. B (The Journal of Research, PJTSAU, 2023)
A field experiment was conducted at Regional Agricultural Research Station, Palem, Nagarkurnool, Southern Telangana Agro Climatic Zone of Telangana State during kharif 2018-19 and 2019-20 to study the performance of super early pigeonpea in different sowing windows and with integrated nutrient management practices under rainfed situations. The experiment was laid out in strip plot design for pigeonpea in kharif 2018 and 2019 with 3 main treatments i.e., M1 (1st July), M2 (20th July) and M3 (10th August) and four integrated nutrient management practices as sub treatments viz., S1: 75% RDF, S2: 75% RDF + FYM enriched with microbial consortia (1 tonne ha-1), S3: 100 % RDF and S4: 100% RDF + FYM enriched with microbial consortia (1 tonne ha-1) and replicated thrice. The performance of the super early pigeonpea in two years of field study revealed that, among the three sowing dates in main treatments, 1st July i.e., M1 witnessed higher final plant population (per cent) and growth parameters viz., plant height (cm), leaf area per plant (cm2) and dry matter production (g m2) at 30, 60 and 90 DAS. The highest seed, haulm yield (kg ha-1) and harvest index of pigeonpea were superior with 1st July (M1) compared to the other sowing dates i.e., 20th July and 10th August. In the sub treatments application of 100% RDF + FYM enriched with microbial consortia @ 1 tonne ha-1 (S4) reported highest plant height at different stages of crop growth that resulted highest dry matter accumulation at 30, 60 and 90 DAS among the sub treatments in the both the years. The seed and stover yield were significantly higher with the above treatment and was followed by the application of 100% RDF (S3). The interaction between sowing dates and integrated nutrient management was found non significant.